Assessment of nutritional status and food habits of adolescents attending centers for psychosocial care for alcohol and drugs in western Paraná, Brazil - Mirian Cozer; Leda Aparecida Vanelli Nabuco de Gouvêa (Universidade de Brasília, 2010)
.